Simultaneous determination of selected hormones, endocrine disruptor compounds, and pesticides in water mediumat trace levels by GC-MS after dispersive liquid-liquid microextraction - Chormey, Dotse Selali; Buyukpinar, Cagdas; Turak, Fatma; Komesli, Okan Tarik; Bakirdere, Sezgin (SPRINGER, 2017)
The need to enhance food safety has led to major advancements in pesticide productions, and though many benefits have been gained, environmental contamination has also risen from these chemicals that tend to persist in the environment. Some pesticides, together with other chemicals commonly called endocrine disruptor compounds, block the receptor sites of hormones or mimic displaced hormones, leading to imbalanced hormonal levels that result in health disorders and diseases. These chemicals occur at trace levels and are not directly detected by conventional analytical methods. A dispersive liquid-liquid microextraction method was therefore developed for preconcentration of 12 analytes including hormones, endocrine disruptor compounds, and pesticides, to be analyzed by gas chromatography mass spectrometry. This was achieved by optimizing parameters such as extractor solvent type and amount, dispersive solvent type and amount, pH, and salt effect that affect extraction output. The limits of detection and quantification of the developed method were between 0.09 and 3.36 and 0.31 and 11.19 ngmL(-1), respectively. The calibration plots of the analytes also showed good linearity and low percent relative standard deviations. Recovery studies were performed for tap water and wastewater samples, and the percent recoveries recorded were between 84 and 109%.
Keywords: Hormones; Endocrine disruptor compounds; Pesticides; Preconcentration; GC-MS; ORGANOCHLORINE PESTICIDES; WASTE-WATER; ORGANOPHOSPHORUS PESTICIDES; RISK-ASSESSMENT; HEALTH IMPACT; EXTRACTION; RESIDUES; EXPOSURE; DAMAGE; Environmental Sciences & Ecology